Adenomatoid odontogenic tumour: A rare threat to orthodontic treatment planning. (September 2019) - Han, Laura; Downing, Alison; Farr, David; Dasgupta, Kaushik; Stewart, Duncan
This case report aims to increase awareness of how an adenomatoid odontogenic tumour (AOT) can present in a similar fashion to a dentigerous cyst and the importance of accurate histopathological diagnosis. In this case, the AOT resulted in loss of the upper left permanent canine in a patient who already had a congenitally absent upper left second premolar, compromising the original orthodontic treatment plan.